Smart Contracts for Efficient Supplier Relationship Management in the Blockchain - Yerram, Sridhar Reddy (American Journal of Trade and Policy, 2022)
Smart contracts have become a game-changing tool for improving supplier relationship management (SRM) efficiency and transparency within the blockchain ecosystem. This study aims to understand better how intelligent contracts facilitate supplier-buyer communication, increase accountability, and streamline procurement procedures. The study’s primary goals are to examine the advantages and difficulties of smart contracts in supply chain management (SRM), explore how they affect supply chain operations, and determine how these findings may affect industry standards and regulatory frameworks. A review methodology based on secondary data amalgamates extant literature and empirical research on smart contracts for supply chain management. Important discoveries show that smart contracts promote efficiency and cooperation in SRM by automating contract execution, improving transparency, and enabling trustless transactions. To fully utilize intelligent contracts in SRM, however, obstacles, including regulatory ambiguity, scalability constraints, and interoperability concerns, must be resolved. Implementing smart contracts in SRM will require clear regulatory frameworks, the development of standards and interoperability, and funding for research and teaching.